WORKSHOP SISTEM INFORMASI MITIGASI BENCANA BANJIR BERBASIS ANDROID DI KOTA PALEMBANG - Hertati, Lesi; Sondang, Virgus Ari; Asharie, Asmawati; Heryati, Agustina (Nindikayla Institute, 2023)
This workshop aims to develop understanding and skills in mitigating flood disasters through the use of an Android-based information system in Palembang City. With the increasing frequency and intensity of flooding in this city, innovative and effective solutions are needed to reduce the negative impacts caused. The methods used in this workshop include theoretical learning about flood disaster mitigation, development of an Android-based information system, as well as case studies of the implementation of similar technology in flood disaster management in other areas. Participants in this workshop were 100 (one hundred) students representing universities in the city of Palembang, involved in direct practice sessions to design, develop and test a prototype of an Android-based information system that could be used in flood disaster situations. The results of this community service are to increase understanding of the importance of technology in disaster mitigation, as well as skills in designing and using Android-based applications to assist the flood disaster mitigation process in Palembang City.